Malignant Extra Renal Rhabdoid Tumour Presenting as Central Airway Obstruction. (27th August 2014) - Madan, Karan; Bal, Amanjit; Agarwal, Ritesh; Das, Ashim
Abstract : Rhabdoid tumours are one of the most aggressive childhood neoplasms associated with high mortality. The commonest age group affected is children less than five years of age. Rhabdoid tumour presenting as an endoluminal tracheal mass leading to central airway obstruction has not been previously reported. We describe the case of a 17-year-old male patient where malignant rhabdoid tumour masqueraded as bronchial asthma leading to a delayed diagnosis of upper airway obstruction by tracheal growth. Histopathological examination and immunohistochemistry confirmed the diagnosis of malignant rhabdoid tumour.